Debate-Café Berbasis Student-Centered Learning untuk Meningkatkan Keterampilan Berbicara Siswa SMA - Wira Manik; Candra Ronitua Gultom; Asnita Hasibuan; Widia Fiski Nainggolan; Enjelika Noella (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Speaking skill is an essential productive competence for senior high school students, particularly in debate text learning. This study aims to improve the speaking skills of eleventh-grade students at SMA Nurcahaya through a Student-Centered Learning approach integrated with the Debate-Café technique. This study employed Classroom Action Research conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The subjects were 36 eleventh-grade students at SMA Nurcahaya. Data were collected through learning activity observation sheets, field notes, and speaking performance tests covering fluency, articulation and intonation, argument reasoning, and communication ethics. The data were analyzed using descriptive quantitative and qualitative techniques. The findings revealed improvements in both learning process quality and learning outcomes. In the pre-cycle phase, the class average score was 63.5 with classical completeness of 33.33%. After Cycle I, the mean score increased to 72.1 with classical completeness of 61.11%. In Cycle II, after strengthening argument scaffolding and debate ethics, the mean score rose to 82.4 with classical completeness of 88.89%, exceeding the mastery criterion of 75. These findings indicate that the Student-Centered Debate-Café technique effectively improves students speaking skills, strengthens argumentative confidence, and creates a more interactive, respectful, and student-centered debate classroom.